Consumer deceleration and well-being under the conditions of control over consumption, social class, and spirituality: A social acceleration perspective - Faisal Qadeer; Laiba Khan; Imran Hameed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This paper explains how and when consumer deceleration - the perception of slowed-down temporal experience - adds to consumer well-being. This investigation is the first attempt to quantify consumer deceleration (a recently coined concept). Secondly, it has utilized social acceleration theory, which is relatively less utilized in the Eastern context, to investigate the consequences of consumer deceleration empirically. Specifically, we argue that consumer deceleration can safeguard consumers from the clutches of fast-moving life, enable them to connect to their inner self, discover their spiritual self, slow down their movement, relax them, and consequently add to consumer well-being. We suggest that the deceleration-well-being path is intervened by consumers' control over consumption (an anti-consumption attitude towards impulsive buying). This mechanism will be attenuated for higher social classes and spirituality. Our evidence is based on a self-administered questionnaire survey utilizing drop-and-collect and via emails (n=299). Data was analyzed through the Hayes Process macro in SPSS, and the findings support our notion that consumer deceleration increases well-being under the underlying conditions except for social class. We provide the theoretical and practical implications of these results. We also suggest some potential research avenues around consumer deceleration.
Keywords: 330; Consumer deceleration; consumer well-being; control over consumption; spirituality; social acceleration theory